PELANGGARAN KODE ETIK OLEH HAKIM MAHKAMAH KONSTITUSI SEBAGAI PERBUATAN MELAWAN HUKUM BERUPA NEPOTISME - Alfret (Veritas et Justitia, 2024)
A code of ethics is a set of written regulations binding members of certain professions, including state officials and judges. For ethical violations by the Constitutional Court judges in Indonesia, an ethics tribunal known as the Honorary Council of the Constitutional Court (MKMK) is authorized to determine whether a breach of the code of ethics has occurred. This study examines whether ethical violations committed by judges as state officials, as determined by the MKMK, can also be prosecuted as unlawful acts, specifically nepotism. Using a normative juridical research method, this study analyzes positive law regarding nepotism as outlined in Law Number 28 of 1999 concerning State Organizer Who is Clean and Free from Corruption, Collusion, and Nepotism, and employs a case study approach, focusing on ethical violations by the Chief Justice of the Constitutional Court, Anwar Usman, as documented in MKMK Decision Number 02/MKMK/L/11/2023. The findings reveal that ethical violations by state officials, such as Constitutional Court judges, may be classified as unlawful acts, including nepotism, provided the ethical violation is substantiated by a formal decision from the ethics tribunal confirming the breach.